Replication Data for: Haplotypes at the Phg-2 locus are determining pathotype-specificity of angular leaf spot resistance in common bean - Nay, Michelle Maria; Raatz, Bodo; Studer, Bruno; Mukankusi, Clare Mugisha (International Center for Tropical Agriculture, 2019)
Data on a study to identify angular leaf spot (ALS) resistant germplasm and genetic mapping of ALS resistance genes